The Prevalence of Ehrlichia/Anaplasma spp. Infection in Dogs Associated with Uveitis - Prasroedsang, Sudarat; Kromkhun, Pudcharaporn; Sritrakoon, Natthanate; Nimsuphan, Burin (Journal of Mahanakorn Veterinary Medicine, 2019)
The infection of Ehrlichia spp. or Anaplasma spp. in 70 dogs brought into an Ophthalmology Clinic, Veterinary Teaching Hospital, Kasetsart University, Bangkhen were studied. All studied dogs were suspected for the infection and showed the ocular sign of uveitis. Dogs were divided into two groups, group 1: 26 dogs showed anterior uveitis and group 2: 44 dogs showed posterior uveitis. Eleven dogs (15.71%) showed positive results when the morula stage of Ehrlichia spp. or Anaplasma spp. were detected by blood smear Wright-Giemsa staining under microscopic examination. However, 41 dogs (58.57%) were found positive when detected the parasites by nested-PCR assay using 16s rRNA gene. Only Ehrlichia canis and Anaplasma platys were detected by nested-PCR and DNA sequencing in 35 (50%) and 6 (8.57) dogs, respectively. In the present study, most of Ehrlichia/Anaplasma spp.-infected dogs associated with uveitis were 1 to 7-year-old and ticks were detected between the physical examination or dogs had history of tick infestation. The results from present study, Ehrlichia/Anaplasma spp. were the main etiology of uveitis which E. canis was the important species causing uveitis in infected dogs. The infection rates of dogs associated with anterior uveitis or posterior uveitis were 57.69% and 59.09%, respectively.